Rice Genome Organization: the Centromere and Genome Interactions - KURATA, NORI (Ann Bot, 2002)
Over the last decade, many varied resources have become available for genome studies in rice. These resources include over 4000 DNA markers, several bacterial artificial chromosome (BAC) libraries, P‐1 derived artificial chromosome (PAC) libraries and yeast artificial chromosome (YAC) libraries (genomic DNA clones, filters and end‐sequences), retrotransposon tagged lines, and many chemical and irradiated mutant lines. Based on these, high‐density genetic maps, cereal comparative maps, YAC and BAC physical maps, and quantitative trait loci (QTL) maps have been constructed, and 93 % of the genome has also been sequenced. These data have revealed key features of the genetic and physical structure of the rice genome and of the evolution of cereal chromosomes. This Botanical Briefing examines aspects of how the rice genome is organized structurally, functionally and evolutionarily. Emphasis is placed on the rice centromere, which is composed of long arrays of centromere‐specific repetitive sequences. Differences and similarities amongst various cereal centromeres are detailed. These indicate essential features of centromere function. Another view of various kinds of interactive relationships within and between genomes, which could play crucial roles in genome organization and evolution, is also introduced. Constructed genetic and physical maps indicate duplication of chromosomal segments and spatial association between specific chromosome regions. A genome‐wide survey of interactive genetic loci has identified various reproductive barriers that may drive speciation of the rice genome. The significance of these findings in genome organization and evolution is discussed.